(untitled) (International Journal of Engineering and Computer Science, 2017)
The aim of my paper is to show how to perform a crashworthiness simulation in the automobile industry using Finite Element Method, Repetitive braking of the vehicle leads to heat generation during each braking event. The resulting rise in temperatures has very significant role in the performance of the braking system. Problems such as premature wear of brake pads and thermal cracking of brake discs are attributed to high temperatures. Consequently controlling the temperature profiles and thermo-mechanical stresses are critical to proper functioning of the braking system. CAE simulations are often used for evaluating the brake disc design using thermo-mechanical analysis techniques. Conventional approach is to use three dimensional FE models of the brake discs. This approach has major drawbacks of higher pre and post processing as well as solution times. Need is felt to develop a quick and reliable method to evaluate the thermal stresses in brake discs. This paper describes one such approach based on modified FEM axisymmetric analysis. This paper reviews numerical methods and analysis procedures used in the study of automotive disc brake. It covers Finite element Method approaches in the automotive industry, the complex Contact analysis. The advantages and limitations of each approach will examine. This review can help analysts to choose right methods and make decisions on new areas of method development. It points out some outstanding issues in modelling and analysis of disc brake squeal and proposes new conceptual design of the disk braking system. It is found that the complex Contact analysis is still the approach favoured by the automotive industry.